Aplikasi Penyadap Telepon dengan Memanfaatkan Teknologi Radio Stream Berbasis Web - Bambang Sugiantoro; Desti Maulida (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2007)
Last several year, the happening terrorism around the society required security officers to act firmer andfind strategy to fight this crime. One of the strategies used was by listening to the committer’s telephone. Tosupport the strategy, it needs advanced technology to help security officer. Therefore, it was important to designand build an application to listen the telephone of the committer, which can be use from far away so that securityofficer can find out the step carried out by the committer and can prepare anticipation step.This application was made using radio stream technology combined with wiretaping equipment attachedto the telephone line of the committer. In making this application, the method of system development used wasWaterfall method. Support application used were Winamp, SHOUTcast server and SHOUTcast Source forWinamp. While, to manage database of the user, it was use PHP and MySQL.From this study, it had been made an application to listen to the telephone of committer using radiostream technology and based on web to help the user to obtain information needed. In using this application, itneeded several computers having role as server, broadcaster and user. The input was in the form of login userand password in the system. Its output was in the form of voice from the telephone user.Keyword: radio streaming, wiretape, telephone